The genera Eriochrysis P. Beauv., Imperata Cirillo and Saccharum L. (Poaceae - Andropogoneae - Saccharinae) in the state of Rio Grande do Sul, Brazil - Welker,Cassiano Aimberê Dorneles (2012)
The subtribe Saccharinae belongs to the tribe Andropogoneae and comprises ca. 140 species in 13 genera, including Eriochrysis, Imperata and Saccharum. This work presents a survey of the species of these three genera in the state of Rio Grande do Sul. Intensive field collections were made in different physiographic regions of the state, as well as studies in several herbaria. The occurrence of three native species of each genus was confirmed in Rio Grande do Sul, in addition to sugar cane (Saccharum officinarum) that is cultivated in the region. Based on the material examined, Eriochrysis villosa is reported for the first time in the state of Paraná, Brazil. Identification keys for the species, descriptions, data on their geographical distributions, habitats and flowering and fruiting periods, as well as illustrations of important taxonomic characters are provided.